6(2g+2)-5g=3(4g-5)-3

Simple and best practice solution for 6(2g+2)-5g=3(4g-5)-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2g+2)-5g=3(4g-5)-3 equation:



6(2g+2)-5g=3(4g-5)-3
We move all terms to the left:
6(2g+2)-5g-(3(4g-5)-3)=0
We add all the numbers together, and all the variables
-5g+6(2g+2)-(3(4g-5)-3)=0
We multiply parentheses
-5g+12g-(3(4g-5)-3)+12=0
We calculate terms in parentheses: -(3(4g-5)-3), so:
3(4g-5)-3
We multiply parentheses
12g-15-3
We add all the numbers together, and all the variables
12g-18
Back to the equation:
-(12g-18)
We add all the numbers together, and all the variables
7g-(12g-18)+12=0
We get rid of parentheses
7g-12g+18+12=0
We add all the numbers together, and all the variables
-5g+30=0
We move all terms containing g to the left, all other terms to the right
-5g=-30
g=-30/-5
g=+6

See similar equations:

| 22x-3=135 | | 4(w-1)=8w+28 | | |B+3|=|2j+3| | | 21x+35=97 | | 2(m+6)-2(m-4)=20 | | 2-(4/3)x=-(5+13/15 | | 2m+6-2m-4=20 | | (3x-10)+(2x)+50=180 | | 3(x-7)-5x=-1 | | x-3/4=-1/12 | | 3x=14+(x+2) | | y/6.5+2=4 | | 1/2+11/2n=-10 | | 5x6=x2 | | 6y+4(y+2)=-22 | | 39=6×x | | 1/2n+11/2=-10 | | -f-3=-6+2f | | -7u+2(u-2)=31 | | 3t+7=2t+27 | | 5(a=4)=3(6+a) | | 2y=2y-3 | | 2(5x+3)+2=3(3x+2)+1x | | -5x-115=205 | | N+2n+3n4n=2+3+4+5+6 | | -5(x+2)+1=3x-8x-11 | | 2y=5y-3y | | -9u+4=4+4u | | 5y-3y-11=18.14 | | 10y-260=10-20y | | 4+3x-10=9x | | c=180 |

Equations solver categories